2016
DOI: 10.1038/srep35662
|View full text |Cite
|
Sign up to set email alerts
|

Dim light at night disturbs the daily sleep-wake cycle in the rat

Abstract: Exposure to light at night (LAN) is associated with insomnia in humans. Light provides the main input to the master clock in the hypothalamic suprachiasmatic nucleus (SCN) that coordinates the sleep-wake cycle. We aimed to develop a rodent model for the effects of LAN on sleep. Therefore, we exposed male Wistar rats to either a 12 h light (150–200lux):12 h dark (LD) schedule or a 12 h light (150–200 lux):12 h dim white light (5 lux) (LDim) schedule. LDim acutely decreased the amplitude of daily rhythms of REM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 65 publications
11
83
2
4
Order By: Relevance
“…These studies found no effects of "dim" ALAN (5 lx.) on total sleep duration in rats (Stenvers et al, 2016) or mice (Borniger, Weil, Zhang, & Nelson, 2013), which is consistent with the idea that ALAN may have little or no negative effect on sleep in nocturnal animals (Borniger et al, 2013). However, exposure to "dim" ALAN affected sleep-wake rhythms in rats, causing them to redistribute daytime sleep into the night (Stenvers et al, 2016).…”
Section: Laboratory-based Sleep Studies: Mechanisms and Physiologysupporting
confidence: 82%
See 3 more Smart Citations
“…These studies found no effects of "dim" ALAN (5 lx.) on total sleep duration in rats (Stenvers et al, 2016) or mice (Borniger, Weil, Zhang, & Nelson, 2013), which is consistent with the idea that ALAN may have little or no negative effect on sleep in nocturnal animals (Borniger et al, 2013). However, exposure to "dim" ALAN affected sleep-wake rhythms in rats, causing them to redistribute daytime sleep into the night (Stenvers et al, 2016).…”
Section: Laboratory-based Sleep Studies: Mechanisms and Physiologysupporting
confidence: 82%
“…on total sleep duration in rats (Stenvers et al., ) or mice (Borniger, Weil, Zhang, & Nelson, ), which is consistent with the idea that ALAN may have little or no negative effect on sleep in nocturnal animals (Borniger et al., ). However, exposure to “dim” ALAN affected sleep–wake rhythms in rats, causing them to redistribute daytime sleep into the night (Stenvers et al., ). Such effects on sleep timing could have important ecological consequences, including increased competition between diurnal and nocturnal species.…”
Section: Laboratory‐based Sleep Studies: Mechanisms and Physiologysupporting
confidence: 72%
See 2 more Smart Citations
“…In addition, rodent studies showed that chronic exposure to LAN reduces the amplitude of the sleep/wake rhythm [46], increases body weight and decreases glucose tolerance [4, 5]. Acute exposure to LAN has been shown to alter the profiles of the hormones melatonin and corticosterone [7, 8].…”
Section: Introductionmentioning
confidence: 99%